2020
DOI: 10.1002/admi.202000080
|View full text |Cite
|
Sign up to set email alerts
|

Charge State Control of F16CoPc on h‐BN/Cu(111)

Abstract: The use of molecular materials in solar cells and nano‐electronics demands a fundamental understanding and control of their electronic properties. Particularly relevant is the molecular response to the environment, that is, the interaction with the support and adjacent molecules, as well as the influence of electrostatic gating. Here, the control of molecular level alignment and charge states of fluorinated cobalt phthalocyanines (F16CoPc) on atomically thin hexagonal boron nitride (h‐BN) sheets on Cu(111) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 57 publications
4
18
1
Order By: Relevance
“…37 V for 2, and 0.39 V for 3, see Figure 6) agree well with the previously reported MO shifts on hBN/Cu(111) (ranging from 0.25 to 0.4 V [28,[35][36][37]) and reflect the local work function variation across the moiré pattern [25,29,30]. In a recent study on F 16 CoPc/hBN/Cu(111), we demonstrated that the local work function difference between the pore and wire regions was preserved upon molecular adsorption [37]. Note, that the smaller shift for the molecule 1 was attributed to the larger distance of the respective wire spectrum from the real wire position (vide supra).…”
Section: Spectroscopic Investigations and Determination Of The Molecusupporting
confidence: 92%
See 4 more Smart Citations
“…37 V for 2, and 0.39 V for 3, see Figure 6) agree well with the previously reported MO shifts on hBN/Cu(111) (ranging from 0.25 to 0.4 V [28,[35][36][37]) and reflect the local work function variation across the moiré pattern [25,29,30]. In a recent study on F 16 CoPc/hBN/Cu(111), we demonstrated that the local work function difference between the pore and wire regions was preserved upon molecular adsorption [37]. Note, that the smaller shift for the molecule 1 was attributed to the larger distance of the respective wire spectrum from the real wire position (vide supra).…”
Section: Spectroscopic Investigations and Determination Of The Molecusupporting
confidence: 92%
“…The colored bars in Figure 5 highlight the energy positions of these frontier orbitals (determined as the bias voltage at the half maximum of the MO leading edge). The observation of well-defined, narrow molecular resonances and large HOMO-LUMO gaps evidenced a reduction of the electronic molecule-support interactions by the hBN spacer layer, as previously reported for adsorbates on hBN/Cu(111) [28,[35][36][37][38] and other hBN/metal supports [18][19][20]79,80]. The dI/dV modulations observed within the gap were attributed to the hBN/Cu(111) support and tip states, respectively (vide infra).…”
Section: Scanning Tunneling Spectroscopic Measurementssupporting
confidence: 77%
See 3 more Smart Citations